'Everything I enjoy doing I just couldn't do': Biographical disruption for sport-related injury. (July 2020) - Malcolm, Dominic; Pullen, Emma
This article draws on interview data with a population of non-elite sport/exercise participants (n = 20) to illustrate the interrelationship between biographical disruption and sport-related injury. It argues that contrary to the significance implied by their lack of prominence on current public health agendas, sport-related injuries can have a devastating personal impact, comparable to the more extreme variants of biographical disruption depicted in the literature on chronic illness. It seeks to explain the apparent incongruence between biophysical severity and subjective assessment of impact, by invoking notions of community normalisation and imagined futures, and identifying the unavailability of what subjects evaluate as effective medical support. These factors combine to problematise the attainment of biographical repair. It further highlights how biographical contingencies such as youthfulness, distinction through exhibiting responsible citizenship and the sense of failure to exert bodily self-management through exercise, perpetuate and escalate both biographical disruption and chronic illness. The paper thus illustrates the aetiological interdependence of biographical disruption and chronic illness as exercisers exacerbate relatively minor ailments due to their reluctance to modify habitual routines.